The learning in hospitalized children with cancer - Bernales Oré, Claudia (2018)
The child with cancer that, as a result of the hospitalization, has been suddenly forced to abandon his home, his province, their customs; that has experienced family separation due to the schedules of the health center; that is opposite to medical procedures necessary for its treatment, where you will experience pain and generalized discomfort; shall, inevitably, high levels of stress and anxiety, symptoms of psychological and behavioral clear that will produce the blockade of important processes at cerebral level, preventing the regular learning. However, are identified substantial factors that produce this blockade, so as to put in place mechanisms adapted to teaching and activate the learning process in hospitalized children with cancer.